Using the quadratic formula, I must find the answer to 3x(squared) -4x-5=0 in simplified square root form

Thank you for the opportunity to help you with your question!

3x^2-4x-5=0

d= 16-4*3*-5 = 16+60 = 76

x= (-(-4) +- sqrt 76)/2*3

= (4 +- 2 sqrt19)/6

= (2+- sqrt19)/3

= (2+ sqrt 19)/3, (2- sqrt 19)/3

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up